Molecular characterization of two cloned nitrilases from Arabidopsis thaliana: key enzymes in biosynthesis of the plant hormone indole-3-acetic acid. - Bartling, D (1994)
As in maize [Wright, A.D., Sampson, M. B., Neuffer, M. G., Michalczuk, L., Slovin, J. P. & Cohen, J. D. (1991) Science 254, 998-1000], the major auxin of higher plants, indole-3-acetic acid, is synthesized mainly via a nontryptophan pathway in Arabidopsis thaliana [Normanly, J., Cohen, J. D. & Fink, G. R. (1993) Proc. Natl. Acad. Sci. USA 90, 10355-10359]. In the latter species, the hormone may be accessible from the glucosinolate glucobrassicin (indole-3-methyl glucosinolate) and from L-tryptophan via indoleacetaldoxime under special circumstances. In each case, indole-3-acetonitrile is the immediate precursor, which is converted into indole-3-acetic acid through the action of nitrilase (nitrile aminohydrolase, EC 3.5.5.1). The genome of A. thaliana contains two nitrilase genes. Nitrilase I had been cloned earlier in our laboratory. The cDNA for nitrilase II (PM255) was cloned and encodes an enzyme that converts indole-3-acetonitrile to indole-3-acetic acid, the plant hormone. We show that the intracellular location as well as the expression pattern of the two A. thaliana nitrilases are distinctly different. Nitrilase I is soluble and is expressed throughout development, but at a very low level during the fruiting stage, while nitrilase II is tightly associated with the plasma membrane, is barely detectable in young rosettes, but is strongly expressed during bolting, flowering, and especially fruit development. The results indicate that more than one pathway of indole-3-acetic acid biosynthesis via indole-3-acetonitrile exists in A. thaliana and that these pathways are differentially regulated throughout plant development.